Meningkatkan Hasil Belajar IPA melalui Model Discovery Learning pada Siswa Kelas 5 Sekolah Dasar - Hartini, Hartini (Social, Humanities, and Educational Studies (SHES): Conference Series, 2020)
This study aims to improve science learning outcomes using the discovery learning model for fifth grade students of SD Negeri I Biting in the 2019/2020 academic year. This type of research is collaborative classroom action research. The research design uses the Kemmis and Mc Taggart model. The method of collecting data is through observation and tests. In the first cycle there were 7 students from 14 people who achieved the completeness of the KKM, namely the percentage of 50%. While the other 7 students have not achieved completeness that is 50%. Meanwhile, in the second cycle, there was an increase in learning outcomes. Of the 14 students have achieved completeness 12 people or 86%. There are only 2 students who have not achieved complete learning outcomes, namely 14%. In the first cycle, student learning outcomes only reached 50% to 86% in the second cycle, meaning that there was an increase in the percentage of completeness about 36% in the second cycle. Based on these results, it can be concluded that the use of discovery learning learning models can improve science learning outcomes for fourth grade students at SDN 1 Biting.